Biocontrol of Collectrotichum gloeosporioides in olive fruits by antagonistic yeasts - Pesce, Virginia Mercedes (2015)
Anthracnose, caused by Colletotrichum sp., is the major fungal disease in all olive producing areas of the world. In Argentina, this disease was reported in Catamarca, La Rioja, Córdoba, Mendoza and San Juan. Biological control using antagonistic microorganisms has been developed as an alternative to synthetic fungicide treatment. Yeasts have characteristics that give them advantages over other microorganisms to exert biocontrol of pathogenic fungi. However, yeasts-like fungi (Aureobasidium) have been reported against Colletotrichum species in olive fruits. The aim of this work was to evaluate the ability of autochthonous yeasts to control C. gloeosporioides in mature olive fruits, at different concentrations. Methodology: 92 antagonistic indigenous yeasts were previously selected in in vitro tests: 45 yeasts from viticultural environments and 47 from olivicultural environments. An isolate of C. gloeosporioides from the collection of INTA IMyZA, Castelar was used as pathogen. The pathogenicity of C. gloeosporioides was evaluated in olive fruits. The fungus was inoculated at different concentrations (10 2 to 10 6 conidia/mL) in mature fruits, and incubated during 5 days at 25°C. Percentage incidence [(number of decayed wounds/number of total wounds) x 100] and the mean of lesion diameter were determined. A suspension of yeasts (10 8 cells/mL) and 10 5 conidia/mL of fungi were inoculated in wounded fruits for biocontrol at in vivo tests (5 days, 25°C). Wounded fruits inoculated with fungal spore suspension were included as negative controls. The incidence of disease and %severity [(mean of diameter lesion in treated fruits/mean of diameter lesion in negative control) x 100] was calculated. A minimum of 50% reduction in the incidence of the disease was considered as antagonistic activity. The influence of yeast concentration at 10 7 and 10 6 cells/mL on biocontrol activity was evaluated. All experiments were made by triplicate. Nine indigenous yeasts (Pichia membranifaciens BPm6; Saccharomyces chevalieri BSch25; Torulaspora delbrueckii BTd126; Candida tropicalis Bo13b; Cryptococcus albidus Bo86; Pichia kudriavzevii Bo91, Bo108; Wickerhamomyces anomalus Bo107, Bo156) reduced the incidence of C. gloeosporioides. Biocontrol efficacies of these yeasts were: 50%, 50%, 63.34%, 90%, 76.67%, 53.34%, 70%, 60% and 90%, respectively. All antagonistic yeasts (except W. anomalus Bo107) were significantly effective in reducing the lesion diameter at 10 8 cells/mL. Only C. tropicalis Bo13b was antagonistic at lower concentration (10 7 cells/mL) with 70% incidence reduction. It can be concluded from this study that indigenous yeasts were effective as in vivo biocontrol agents against C. gloeosporioides. Concentrations of antagonists significantly affected their biocontrol activity. This is the first report that informed autochthonous biocontrol yeasts against C. gloeosporioides in olive.